Green Tourism Development as Community Empowerment Efforts in Pemuteran Village, Buleleng, Bali - Suwena, I Ketut; Arismayanti, Ni Ketut (Udayana Journal of Social Sciences and Humanities, 2017)
Pemuteran has tourism potential and stunning natural beauty. Pemuteran village communities have not been involved in tourism activities resulting maximum untapped tourist potential to the maximum, limited opportunity society are involved in tourism development, and creativity in tourism in the village. This research is objective to maximize the role of the community in various aspects of tourism development. The development of tourism is expected to: (1) empowering local communities; (2) diversification of rural tourism products; (3) demonstration model to develop green tourism; (4) produce a tourism product of high quality and competitiveness; (5) the development of a more responsible and sustainable tourism. Data were collected through observation, interviews, questionnaires, literature studies, and technical documentation. Data were analyzed using qualitative descriptive analysis of IFAS, EFAS, and SWOT. The strategy resulted in the development of green tourism as an effort to increase community empowerment in economic activity in the village of Pemuteran is green tourism marketing strategy; Strategy creation and development of green tourism products; Strategy commitment and development of community-based tourism development in North Bali; The strategy for improving the quality of human resources through the mastery of information technology and entrepreneurship; Waste management strategy together and independently; Infrastructure development strategy based tourism green tourism; Strategy green tourism travel packages in Buleleng. Advice can be given is the importance of the commitment in the development of tourism development in North Bali-based green tourism; the need for management of solid waste management; the need for the identification and development of a tourist attraction; importance of improving the quality of human resources that are highly competitive; the importance of increasing public participation in the planning, implementation and monitoring of tourism development in the region.